Type IV singular bouncing cosmology from f ( T ) Gravity - Logbo, P.H.; Houndjo, M.J.S. (arXiv, 2018)
We investigate bouncing scenario in the modified f(T ) gravity, T being the torsion scalar. Attention is attached to the reconstruction of f(T ) able to describe type IV singular bouncing evolution, where we adopt as assumption that the bouncing and type IV singularity points coincide. In the context of the reconstructed f(T ) model we calculate the Hubble slow-roll parameters in order to determine the dynamical evolution of the cosmological system under study. The results show that the Hubble slow-roll parameters become singular at the type IV singularity indicating a dynamical instability. Moreover we perform the stability analysis of the f(T ) gravity solution where, according to the obtained result, the type IV singularity point is a saddle point in agreement with the bounce scenario.
Bouncing cosmology [1–10] is an important way to solve initial singularity problem, which in the view of cosmological theories, is an undesirable characteristic. According to the bouncing cosmology the universe presents a contracted phase which ends up to a minimal radius, and after that starts an expanded phase. This means that the collapsing feature of the universe never occurs, reveling the impossibility of initial singularity.
Keywords: Bouncing cosmology; torsion scalar